Vehicle dynamics modelling of an electric driven race car - Szántó, Szántó; Szíki, Gusztáv Áron; Hajdu, Sándor (International Journal of Engineering and Management Sciences, 2016)
In the following we are presenting a vehicle dynamics simulation program developed in MATLAB environment. The program is capable of calculating the dynamics functions of a vehicle from its technical data. The program has been successfully applied for the optimization of the technical data of an electric driven race car that was designed and constructed at the Department of Mechanical Engineering of the University of Debrecen.